Breaking the Wall of Poverty: Microfinance as Social and Economic Safety Net for Financially Excluded People in Nepal - Karki, Karun Kishor; Dhungana, Nirajan; Budhathoki, Bhesh Bahadur (Molung Educational Frontier, 2021)
Microfinance is a financial service aimed at economically underprivileged people who have no or limited access to formal financial institutions such as banks due to the lack of financial resources, collateral, or low income. Microfinance institutions provide a collateral-free loan to low-income individuals with the principle of financial inclusion, which allows them to invest in various self-employment activities. In this article, we critically review the development of microfinance and its issues and challenges in Nepal. More specifically, using the concept of the Grameen Bank model and its relevance in the context of Nepali microfinance institutions, we explore how microfinance can be an effective tool of financial intervention to alleviate rural poverty in Nepal. Methodologically, we utilize secondary data sources such as government and non-government reports and existing empirical studies. We offer recommendations for policymakers to establish appropriate modalities, programs, and microfinance services targeting the socio-economic transformation of rural communities in Nepal. We conclude that the government and financial institutions can stimulate microfinance institutions through multidimensional interventions and facilitation to advance the socio-economic status of financially underprivileged people in rural communities in Nepal.